Cultivation of shiitake using sawdust from Widely available local woods in Argentina - D. G. Pire (Micología Aplicada International, 2001)
The cultivation of shiitake (Lentinula edodes) in Argentina began in recent years; however, treespecies commonly used as substrates in Southeast Asia or North America are not present. Weassayed eight types of easily available local woods: "coihue" (Nothofagus dombeyi), "lenga" (N.pumilio), "ñire" (N. antarctica), "roble pellín" (N. obliqua), eucalypt (Eucalyptuscamaldulensis), pine (Pinus ellioti), "Paraná pine" (Araucaria angustifolia), and willow (Salixbabylonica). Two strains of shiitake were studied, using experimental blocks (1 kg) which containedthe following substrate formulation: 80% sawdust, 10% wheat bran, 10% millet seed,2% chalk, adjusted to 74% moisture. Blocks were incubated at 25 C for a month, and thensubjected to a cold shock at 5 C for 7-10 days in order to promote fruiting. After induction, theblocks were placed in a room at 18±3 C, about 9 h/day of lighting, and watered daily. Fruitbodies were obtained from most wood types studied, with the exception of "Paraná pine" andpine. The strain BAFC-2250 had higher biological efficiencies (BE), which were recorded in"roble pellín" (60.4%), "lenga" (52.3%), and eucalypt (26.5%). The highest mushroom yieldwas also shown by the strain BAFC-2250.